Amor, poder e violência em contos de Nélida Piñon - Joyce Glenda Barros Amorim (2015)
The research object of the dissertation is the articulation between three recurrent aspects of Nélida Piñon' short story literary work: Love, Power and Violence. We've analyzed the following narratives: 'Fraternidade' and 'A moça e seu fruto, from 'Tempo das frutas' (1966); 'Colheita', 'Sangue esclarecido' and 'Luz', from 'Sala de armas' (1973); as well as 'O Jardim das Oliveiras' and 'O revólver da paixão', from O calor das coisas (1980). In order to analyze those literary works, we refer to concepts developed by Erich Fromm, Gérard Lebrun, Roland Barthes, Heleieth Saffioti, Nilo Odalia, Denis de Rougemont, R. Howard Bloch, Francesco Alberoni, Marcel Conche, Karl Erich Schollhammer, Márcio Seligmann-Silva, Maria Rita Kehl, Jaime Ginzburg, and others. It was possible to state that, in the selected short stories, there's a suggestion of love (or its absence and negation) as a form of power. A form of dominance of others, in order to influence their behavior. It was also noticed that power establishes itself through forms of punishment and psychological and/or physical violence. This occurs especially due to the characters' psychopathologies, in which they take pleasure dominating and/or harassing other human beings, and, by doing so, (re)claim their own identities.